The, study of the investment portfolio of life insurance business in Malaysia / David Mathew Baru … [et al.] - Baru, David Mathew; Jaapari, Awang; Druce, Lucas; Sarkinah, Shamsul; Siros, Presley (1985)
"The -first rumblings of the Insurance Industry in Malaysia did not take place until the 18th. Century. Hitherto, Insurance activities were largely non-existent. The Insurance industry then was mainly based on the British system because of the advent oi Colonialism. Local participation was negligible because of ignorance and lack of expertise. The 1950's witnessed the spiraling growth in the industry. A substantial 'portion of the market was cornered by British and American firms although locally Incorporated Companies were making their presence felt. After independence in 1957, nationalistic sentiment resulted in moves to content the establishment of wholly-owned subsidiaries or branches of foreign companies which- had previously been allowed a ,free reins. Given much encouragement, the domestic companies were poised to make further inroads into the' market. However, the boom was marred by many companies which did not have sound underwriting practice. A number of companies went out of business leaving their policyholders high and dry.